2017
DOI: 10.18632/oncotarget.15833
|View full text |Cite
|
Sign up to set email alerts
|

HER2-specific recombinant immunotoxin 4D5scFv-PE40 passes through retrograde trafficking route and forces cells to enter apoptosis

Abstract: Immunotoxin 4D5scFv-PE40 is a recombinant protein that comprises 4D5scFv antibody as a targeting module and fragment of Pseudomonas exotoxin A as an effector (toxic) one. The immunotoxin has shown pronounced antitumor effect on cancer cells overexpressing HER2 receptor in vitro and on HER2-positive experimental tumors in vivo. We clarified the mechanism of 4D5scFv-PE40 activity that is of particular importance in the case of targeted therapeutic agent aimed at personalizing treatment of disease in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Confocal microscopy images provided further evidence that the nucleus of MDBK cells infected with BoHV-1 was damaged after treatment with 1.00 μM BoScFv-PE38 ( Figure 5D ). These findings clearly indicated the internalization capability of BoScFv-PE38 via entrapment of BoHV-1 after binding to gD, which is similar to the antitumor immunotoxin 4D5scFv-PE40 reported earlier ( Sokolova et al, 2017 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Confocal microscopy images provided further evidence that the nucleus of MDBK cells infected with BoHV-1 was damaged after treatment with 1.00 μM BoScFv-PE38 ( Figure 5D ). These findings clearly indicated the internalization capability of BoScFv-PE38 via entrapment of BoHV-1 after binding to gD, which is similar to the antitumor immunotoxin 4D5scFv-PE40 reported earlier ( Sokolova et al, 2017 ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that cytotoxicity to targeted cells induces apoptosis in virus-infected host cells or cancer cells ( Liu X.F. et al, 2016 ; Sokolova et al, 2017 ); specifically, high levels of ATP and ammonia are the major inducers of apoptosis ( Jin et al, 2017 ; Zhang et al, 2017 ). In our study, BoScFv-PE38 significantly increased the titers of ATP and ammonia in MDBK cells infected with BoHV-1 ( Figures 6A,B ), which implied that apoptosis was triggered in MDBK cells as a result of treatment with BoScFv-PE38 immunotoxin and the effect was dose-dependent ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…57 Tumor necrosis factor (TNF)-based immunotoxins were developed with antimelanoma antibody (scFvMEL), which showed cytotoxicity in nude mice. 58…”
Section: Cytokine Receptor As a Target And Ligand As A Targeting Moietymentioning
confidence: 99%
“…ErbB has higher expression levels in many tumors; ErbB2/ Her2 was targeted by ScFv (FRP5)-ETA for solid tumors. 58 It consists of an N-terminal ScFv, genetically linked to truncated PE. Epidermal growth factor receptor (EGFR) is another growth factor being used widely for solid tumors.…”
Section: Growth Factor Receptors As Targetsmentioning
confidence: 99%
“…As the value of recombinant protein has increased, increasing attention has been paid to their production and purification. Some recombinant proteins have been used as drugs for treating human disease (Bera, Onda, Kreitman, & Pastan, ; Simon & FitzGerald, ; Sokolova et al, ) as well as to evaluate the efficacy and safety of these recombinant protein drugs; >95% purity is essential (Geng & Wang, ).…”
Section: Introductionmentioning
confidence: 99%